Evidence for Evolutionary Pathway-dependent Black Hole Scaling Relations - Jonathan H. Cohn; Emmanuel Durodola; Quinn O. Casey; Erini Lambrides; Ryan C. Hickox (The Astrophysical Journal Letters, 2025)
Recent observations have identified an abundance of high-redshift active galactic nuclei (AGN) with overmassive supermassive black holes (BHs) compared to the local BH mass−total stellar mass ( M _BH – M _⋆ ) relation for AGN. High- z M _BH measurements are critical for probing growth histories of BHs and their host galaxies, including BH seeding and evolution of the M _BH – M _⋆ relation. However, BH masses in high- z AGN are generally estimated from single-epoch measurements, which carry large systematic uncertainties. More reliable M _BH detection methods like dynamical measurements are currently only possible in the local Universe or with strongly lensed systems. Fortunately, new dynamical M _BH measurements in a sample of six local galaxies identified as likely relics of common quiescent red nugget galaxies at cosmic noon, as well as a z  ∼ 2 lensed red nugget, present a complementary probe of high- z relations. We compare the z  ∼ 2 red nugget and relic BHs to recent results for 4 <  z  < 11 AGN, quasi-stellar objects, and little red dots. Intriguingly, the z  ∼ 2 galaxy and local relics all lie on both the local M _BH – M _⋆ relation for bulges and the 4 <  z  < 7 M _BH – M _⋆ AGN relation, although high- z AGN remain overmassive compared to both local relations. We conclude it is unlikely that a uniform M _BH – M _⋆ redshift evolution applies to all galaxies. Since total M _⋆ is affected by growth processes that may not drive BH growth, different evolutionary pathways must be carefully considered when building BH scaling relations.